2019
DOI: 10.2174/1574886314666190520105330
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reaction (ADR) as a Cause of Hospitalization at a Government Hospital in Saudi Arabia: A Prospective Observational Study

Abstract: Background:ADRs represent a substantial burden on health care resources worldwide and are considered as one of the leading causes of morbidity and mortality which significantly affects hospitalization rates. However, ADR related hospital admissions are not well explored in Saudi Arabia.Objective:The current study aims to evaluate ADR-related admissions at King Saud Hospital, Unaizah, Qassim, Saudi Arabia.Methods:A prospective, observational study was conducted at King Saud Hospital Unaizah. Over a period of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
5
19
1
Order By: Relevance
“…It is interesting to note that paracetamol, a widely available over-the-counter drug, was associated with 1.4% of the total serious ADRs, including elevated liver enzyme, rash, renal failure, diarrhea, and hypotension. Our results were compatible with findings of another study conducted in a governmental hospital in Saudi Arabia, which found higher ADR proportion (31.6%) for (NSAIDs, Analgesic) indicating a possible regional phenomenon ( Alayed et al, 2019 ). This might also be related to polypharmacy or serious misuse of over-the-counter medications in Saudi Arabia, which should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting to note that paracetamol, a widely available over-the-counter drug, was associated with 1.4% of the total serious ADRs, including elevated liver enzyme, rash, renal failure, diarrhea, and hypotension. Our results were compatible with findings of another study conducted in a governmental hospital in Saudi Arabia, which found higher ADR proportion (31.6%) for (NSAIDs, Analgesic) indicating a possible regional phenomenon ( Alayed et al, 2019 ). This might also be related to polypharmacy or serious misuse of over-the-counter medications in Saudi Arabia, which should be addressed in future studies.…”
Section: Discussionsupporting
confidence: 92%
“…This will boost identification of ADRs at the national level and will open up a new horizon for research to understand and prevent different ADRs. A recently published national study (R.A. Almubark et al, 2020) for community-based adverse drug reactions in Saudi Arabia targeting community pharmacy visitors estimated that over a quarter (28%) of the sample in the KSA experienced symptoms of at least one ADR in the previous year, which is higher than the prevalence in similar studies in Sweden (7.8%) and Italy (9.9%) [ 26 , 27 ]. Consumer reporting could become crucial for the developing countries to implement a proper and efficient PhV system that could reduce morbidity and mortality as well as the economic burden of ADRs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor recognition and registration of ADRs as the cause of admission could explain this discrepancy. In addition, most of the studies into ADR-related hospital admissions consist of actively reported or actively registered ADRs at the time of admission resulting in a higher chance of recognition than in retrospective data [8,9,[17][18][19][20][21][22]. We studied hospital admissions that are coded after discharge; therefore, our results are also influenced by the method and accuracy of coding by the hospitals.…”
Section: Discussionmentioning
confidence: 99%